Standards for epidemiologic studies and surveillance of epilepsy - Thurman, David J.; Beghi, Ettore; Begley, Charles E.; Berg, Anne T.; Buchhalter, Jeffrey R.; Ding, Ding; Hesdorffer, Dale C.; Hauser, W. Allen; Kazis, Lewis; Kobau, Rosemarie; Kroner, Barbara; Labiner, David; et al. (Epilepsia (Copenhagen), 2011)
Summary Worldwide, about 65 million people are estimated to have epilepsy. Epidemiologic studies are necessary to define the full public health burden of epilepsy; to set public health and health care priorities; to provide information needed for prevention, early detection, and treatment; to identify education and service needs; and to promote effective health care and support programs for people with epilepsy. However, different definitions and epidemiologic methods complicate the tasks of these studies and their interpretations and comparisons. The purpose of this document is to promote consistency in definitions and methods in an effort to enhance future population‐based epidemiologic studies, facilitate comparison between populations, and encourage the collection of data useful for the promotion of public health. We discuss: (1) conceptual and operational definitions of epilepsy, (2) data resources and recommended data elements, and (3) methods and analyses appropriate for epidemiologic studies or the surveillance of epilepsy. Variations in these are considered, taking into account differing resource availability and needs among countries and differing purposes among studies.